2005
DOI: 10.3168/jds.s0022-0302(05)72812-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Concentrate Supplementation on Nutrient Flow to the Omasum in Dairy Cows Receiving Freshly Cut Grass

Abstract: An experiment was carried out to determine the effect of increasing the amount of grain-based concentrate (0, 3, or 6 kg/d) on nutrient flow to the omasum, rumen fermentation pattern, milk yield, and nutrient use of dairy cows. Harvested timothy-meadow fescue grass was fed individually 3 times daily to 6 rumen-cannulated Holstein-Friesian cows in a duplicated 3 x 3 Latin square experiment. Grass was offered as 6 equal meals daily, and concentrates were fed as 2 equal meals daily. Nitrogen, microbial N, and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
7
19
1
Order By: Relevance
“…The animal-derived CH 4 emissions were calculated as follows: the gross energy consumption of cows on pasture feeding was based on results of Sairanen et al (2005). A conversion factor of 6.5% of gross energy as CH 4 was used (Yan et al 2000) which resulted to an estimate of CH 4 production of 160-176 kg CH 4 cow -1 yr -1…”
Section: Discussionmentioning
confidence: 99%
“…The animal-derived CH 4 emissions were calculated as follows: the gross energy consumption of cows on pasture feeding was based on results of Sairanen et al (2005). A conversion factor of 6.5% of gross energy as CH 4 was used (Yan et al 2000) which resulted to an estimate of CH 4 production of 160-176 kg CH 4 cow -1 yr -1…”
Section: Discussionmentioning
confidence: 99%
“…This adjustment represents the potential osmolality decrease in reticulorumen fluid, which in turn enhances net water transfer via the rumen wall (Anil et al, 1993;Storm et al, 2012). The adjusted fractional rate of the net water transfer Agle et al, 2010;Alamouti et al, 2009;Beauchemin et al, 2008;Beauchemin and Yang, 2005;Bowman et al, 2002Bowman et al, , 2003Canale et al, 1988;Casper et al, 1999;Cassida and Stokes, 1986;Couderc et al, 2006;Dado and Allen, 1995;Fernandez et al, 2004;Kammes and Allen, 2012;Kammes et al, 2012a,b;Kargar et al, 2010;Kendall et al, 2009;Kononoff and Heinrichs, 2003a,b;Kononoff et al, 2003;Krämer et al, 2013;Krause et al, 2003;Le Liboux and Peyraud, 1998;Peyraud, 2010, 2011;Lykos et al, 1997;Maekawa et al, 2002;Mathew et al, 2011;Maulfair and Heinrichs, 2013a,b;Maulfair et al, 2010;Mooney and Allen, 2007;Mowrey et al, 1999;Noftsger et al, 2005;Oba and Allen, 2000;Rabelo et al, 2001;Reis and Combs, 2000a,b;Rius et al, 2012;Sairanen et al, 2005;San Emeterio et al, 2000;Soltani et al, 2009;Stensig and Robinson, 1997;…”
Section: Model Developmentmentioning
confidence: 99%
“…Concentrate supplementation (R2) provided adequate ME and MP balances at 20 o C, but the ME balance was slightly below the requirement at 30 o C. Higher ME, CP and soluble protein contents in the ration might be the reason of such response. This was confirmed that concentrate supplementation increased nutrient flow and milk production of dairy cows (Bargo et al, 2002;Sairanen et al, 2005;McEvoy et al, 2008). Supplementation of leguminous tree leaves (R3) did not improve much total ME available compared to R1 (23.7 vs 21.1 Mcal/ day) and, hence, negative energy balance occurred.…”
Section: Nutrient Balancementioning
confidence: 57%
“…This was due to the influence of rate of passage. Low fiber feeds such as concentrate have relatively high rate of passage (Sairanen et al, 2005) and this is correlated to its low peNDF value (Fox et al, 2004). The fact implies that the protein from concentrate is more available post-ruminally while the protein from leguminous leaves is more available in the rumen.…”
Section: Nutrient Balancementioning
confidence: 99%